Appraisal of labor management approaches within the private residential construction firms in the Kathmandu Valley - Sapkota, Sachin; Subedi, Manoj; Ale, Dilip (Journal of Emerging Management Studies, 2023)
Purpose - The purpose of this study was to investigate labor management practices in private housing developers in the Kathmandu Valley. Evaluating perception on current practices, identifying challenges, and proposing solutions to improve labor management were also part of the paper. Design/methodology/approach - The research paper employed a quantitative approach and cross-sectional survey design to investigate the research objective. The researchers used the quota sampling method to select participants from employees and executives working on 17 under-construction projects, allowing for the sample size to be divided and participants to be selected based on specific characteristics. Data were collected from 85 respondents through self-administered questionnaires. Findings - The findings indicate a preference for hiring trained and experienced workers but highlight inadequate communication channels and planning. The study also identifies challenges associated with inadequate wages, occupational health and safety, labor policy, unfair hearing, and insufficient training. The study recommends focusing on employee staffing, performance evaluation, work environment, training, and compensation management as remedial measures to address these challenges. Conclusion - The paper advocates the critical need for improved labor management practices in the private housing sector. The paper highlights several challenges, including low wages, limited communication channels, weak control systems, and inadequate health and safety measures. To address these issues, it is essential to implement appropriate measures such as providing fair wages, offering economic benefits, establishing comprehensive occupational safety and health policies, prioritizing training and development programs, enhancing employee staffing procedures, and implementing effective performance evaluation frameworks. Originality - This research brings originality to the field by examining labor management practices specifically within the private housing sector, a topic that has received limited attention in the context of Nepal.